2023
DOI: 10.1177/02601060231186865
|View full text |Cite
|
Sign up to set email alerts
|

Taste receptors influencing effective modalities in human health – A cutting edge update on TAS1R and TAS2R receptor polymorphisms in taste perception and disease risk

Abstract: Background: Taste is the characteristic sensory modality of the gustatory system associated with dietary intake. The ability of humans to perceive different tastes is predisposed by the activity of taste receptors. The expression of TAS1R family of genes enables the detection of sweetness and umaminess, whereas TAS2R enables the detection of bitterness. The varying levels of expression of these genes within different organs of the gastro-intestinal tract, regulates the metabolism of biomolecules including carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…For instance, for hSTR, it was reported that glucose can bind to the Venus fly trap domain (VFTD) and amino-terminal domain (ATD) of the T1R2 and T1R3 [ 15 , 16 ]. For hBTR, 25 receptors of the hTAS2R family have been identified as capable of binding with various ligands to produce diverse bitter tastes [ 17 , 18 ]. Consequently, the diverse binding patterns between taste receptors and sweetener molecules (ligands) result in distinctive taste signals, leading to variations in sweetness and bitterness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for hSTR, it was reported that glucose can bind to the Venus fly trap domain (VFTD) and amino-terminal domain (ATD) of the T1R2 and T1R3 [ 15 , 16 ]. For hBTR, 25 receptors of the hTAS2R family have been identified as capable of binding with various ligands to produce diverse bitter tastes [ 17 , 18 ]. Consequently, the diverse binding patterns between taste receptors and sweetener molecules (ligands) result in distinctive taste signals, leading to variations in sweetness and bitterness.…”
Section: Introductionmentioning
confidence: 99%